Introjective Individuals Tend Toward Anhedonia: Self-Report and Experimental Evidence - Silva, Jaime R.; Vivanco-Carlevari, Anastassia; Martínez, Claudio; Krause, Mariane (Frontiers in Psychiatry, 2018)
A broad line of research has conceptualized personality based on the interaction of two aspects: interpersonal relatedness and self-definition. This theoretical corpus understands these functions as two poles according to the patterns of interaction and relevance in personality. Additionally, the exacerbation of one of these poles generates a psychopathological model that identifies three types of depressive experience: anaclitic, introjective, or mixed pattern. Understanding the lack of interest as a key symptom of depression, this experiment evaluates a relation for anhedonia and the polarities model configuration using an empirical and experimental protocol. We tested 177 individuals using the Beck Depression Inventory (BDI) subscale for anhedonia and a visual discrimination task with a specific reward system, which was implemented to study reinforcement sensitivity. Participants were classified into four groups by the polarities of experience model. The subscale’s results showed that individuals with an introjective character exhibited an enhanced anhedonic symptomatology but no co-occurrence of this evidence on the experimental protocol. These results empirically support the two polarities of the depressive personality model and raise new questions regarding how to experimentally test this relation.